The island of excess love - Block, Francesca Lia 1962- (Christy Ottaviano books, 2014)
Pen, Hex, Ash, Ez, and Venice are living on hard work, companionship, and dreams in the pink house by the sea until a foreboding ship arrives and all start having strange visions of destruction and violence then, trance-like, they head for the ship and their new battles, with Pen using Virgil's epic Aeneid as her guide